EVALUASI TINGKAT CEMARAN MIKROBA PADA DAGING AYAM YANG DIPASARKAN DI BEBERAPA PASAR DI KOTA DENPASAR - Setyawan I M. E.; S. A. Lindawati; I N. S. Miwada (Animal Science Study Program, Faculty of Animal Husbandry, Udayana University, 2017)
The aimed of this study to analyze the level of microbe’s spreading (TPC, Coliform, E.coli ) and the water degree in chiken which sold in some traditional market in Denpasar. This study took place in Livestock Product Technology and Microbiology laboratory Faculty of Animal Husbandry – Udayana University for 3 months from September until November 2016. The design which was used for this study was a Randomized Block Design (RBD) with 4 treatments and 4 repititions. The 4 treatments were Sanglah market (S), Kreneng market (K), Badung market (B) and Pemedilan market (P). The part of the chicken which was used for this study was the chicken’s chest. This study used 2 step. The first step was descriptive aspects when the cutting process from the beginning until the end was observed fully. The second step was quantitative analysis including TPC (Total Plate Count), Coliform, E. coli and water degree. The results showed that TPC in Sanglah markets was 2.77 x 108 cfu/g, TPC in Kreneng market was 4.52 x 107 cfu/g, TPC in Badung pasar was 7.50 x 107 cfu/g and TPC in Pemedilan market was 4.87 x 107 cfu/g. Coliform in Sanglah market was 7.21 x 106 cfu/g, Coliform in Kreneng market was 4.42 x 106 cfu/g, Coliform in Badung market was 6.17 x 106 cfu/g, and Coliform in Pemedilan market was 5.10 x 106 cfu/g. Escherichia coli in Sanglah market was 6.25 x 105 cfu/g, Kreneng market 4.12 x 105 cfu/g, Badung market 3.55 x 106 cfu/g and Pemedilan market 4.72 x 104 cfu/g. The water degree in Sanglah market 75.39% 74.54% Kreneng market, Badung market 75.50% and Pemedilan market 75.86%. This study concluded that the level of microbe’s spreading in chicken in some some traditional markets in Denpasar was over Indonesia National Standard.